DEVELOPMENT OF TEACHING AND LEARNING-BASED STUDENT WORKSHEETS (LKPD) TO ENHANCE THE CRITICAL THINKING SKILLS OF EIGHTH-GRADE JUNIOR HIGH SCHOOL STUDENTS - Andespa Siregar; Rusydi Ananda (Prima: Jurnal Pendidikan Matematika, 2026)
This research aims to develop a contextual-based Student Worksheet (LKPD) on the topic of Systems of Linear Equations in Two Variables (SPLDV) that is valid, practical, and effective in improving critical thinking skills of eighth-grade junior high school students. This research employs a Research and Development (R&D) approach with the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The research subjects were eighth-grade students of SMP Muhammadiyah 48 Medan, mathematics teachers, and material and media experts. The instruments used included expert validation sheets, teacher and student response questionnaires, and critical thinking skills tests (pre-test and post-test). The results showed that the contextual-based LKPD obtained an average validation score of 92.79% with a very valid category, a practicality level of 85.05% with a very practical category, and effectiveness with an N-Gain score of 0.59 (medium category) and an effectiveness percentage of 59% (quite effective category). Thus, the developed contextual-based LKPD is feasible to be used as an alternative teaching material on SPLDV topics to improve the critical thinking skills of eighth-grade junior high school students.